Label-free detection of prostaglandin transporter (SLCO2A1) function and inhibition: insights by wound healing and TRACT assays - Mocking, Tamara A. M.; van Oostveen, Wieke M.; van Veldhoven, Jacobus P. D.; Minnee, Hugo; Fehres, Cynthia M.; Whitehurst, Charles E.; IJzerman, Adriaan P.; Heitman, Laura H. (Frontiers in Pharmacology, 2024)
The prostaglandin transporter (PGT, SLCO2A1) mediates transport of prostanoids (a.o. prostaglandin E2 (PGE2)) into cells and thereby promotes their degradation. Overexpression of PGT leads to low extracellular PGE2 levels and has been linked to impaired wound healing of diabetic foot ulcers. Inhibition of PGT could thus be beneficial, however, no PGT inhibitors are currently on the market and drug discovery efforts are hampered by lack of high-through screening assays for this transporter.Here we report on a label-free impedance-based assay for PGT that measures transport activity through receptor activation (TRACT) utilizing prostaglandin E2 receptor subtype EP3 and EP4 that are activated by PGE2. We found that induction of PGT expression on HEK293-JumpIn-SLCO2A1 cells that also express EP3 and EP4 leads to an over 10-fold reduction in agonistic potency of PGE2. PGE2 potency could be recovered upon inhibition of PGT-mediated PGE2 uptake with PGT inhibitors olmesartan and T26A, the potency of which could be established as well. Moreover, the TRACT assay enabled the assessment of transport function of PGT natural variants. Lastly, HUVEC cells endogenously expressing prostanoid receptors and PGT were exploited to study wound healing properties of PGE2 and T26A in real-time using a novel impedance-based scratch-induced wound healing assay. These novel impedance-based assays will advance PGT drug discovery efforts and pave the way for the development of PGT-based therapies.